PENGAWASAN LANGSUNG DINAS PERHUBUNGAN KOTA PEKANBARU TERHADAP IZIN ANGKUTAN ANGKUTAN ANTAR JEMPUT DALAM PROVINSI (AJDP) TAHUN 2018 - Reni Angriani; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Pekanbaru City Transportation Agency is a government agency that has the task and function of supervision in the field of Shuttle Transportation within the Province (AJDP) operating in Pekanbaru City. A supervisory role is needed to ensure Transportation within the Province (AJDP) operates in Pekanbaru City in accordance with applicable regulations, thereby ensuring the safety and safety of the people who use these transportation services. This happens because there is still a lack of supervision conducted by the Pekanbaru City Transportation Department. The formulation of the problem in this study is how the supervision of the Pekanbaru City Transportation Department Against 2018 Provincial Transportation and Shuttle (AJDP) and what are the inhibiting factors that affect the supervision of the Pekanbaru City Transportation Department.The purpose of this study was to determine the direct supervision of the Pekanbaru City Transportation Department of the 2018 Provincial Shuttle Transportation Permit (AJDP) and the inhibiting factors that influence the supervision.The concept of the theory that I use for the supervisory function according to Brantas and the concept of Transportation theory according to Adisasmita. This research uses a qualitative approach with descriptive methods. In collecting data, the writer uses interview and documentation techniques.The results of the author's research are the supervision of the Pekanbaru City Transportation Department Against 2018 (AJDP) Transportation within the Province (AJDP). This can be seen from the large number of Transportation within the Province (AJDP) operating in Pekanbaru City which do not have route licenses. The factors that influence this supervision are the condition of Human Resources in the Pekanbaru City Transportation Department. The second factor is the lack of coordination between personnel who served in the supervision section of the Pekanbaru City Transportation Department. The next factor is the lack of community participation in providing information and cooperation to related agencies.  Keywords: supervision, Transportation within the Province (AJDP), Licensing